Sosialisasi Terobosan Baru Nugget Lele Menjadi Pilihan Asupan Gizi Pencegah Stunting di Desa Mentigi - Rahmaniyar, Atik (AL QUWWAH : Jurnal Pengabdian Masyarakat, 2024)
Mentigi village is in Membalong District, Belitung Regency. This village has a problem that is currently widespread in Indonesia, namely stunting. Based on this problem, the IAIN SAS Babel KKN team, assisted by the Membalong District Health Center team, held a socialization regarding the prevention of stunting. by implementing a new breakthrough in processed catfish which is processed into nuggets, where catfish has quite high animal protein, compared to beef, so it can prevent stunting., apart from containing quite high levels of animal protein, catfish also has a cheap price and is easy to cultivate by the people of Menting Village. This socialization also aims to provide in-depth knowledge about stunting. and provide new skills to PKK cadres and Mentigi Village residents in managing catfish into nuggets as a variety of high protein and nutritious food menus to prevent stunting. The method used in socializing this new breakthrough for catfish nuggets as a nutritional intake option is providing didactic examples regarding the causes of stunting and the consequences of stunting and providing examples of how to make catfish nuggets. This action resulted in increasing the understanding of PKK cadres and Mentigi village residents regarding stunting and processing catfish nuggets as a variation of the protein and nutritious food menu in the context of reducing the stunting rate in Mentigi village.Desa Mentigi berada di Kecamatan Membalong, Kabupaten Belitung. Desa ini memiliki problematika yang saat ini sedang marak di Indonesia, yaitu stunting. Dari permasalahan ini, tim KKN IAIN SAS Babel dibantu oleh tim Puskesmas Kecamatan Membalong mengadakan sosialisasi mengenai pencegahan stunting dengan menerapkan terobosan baru dari olahan ikan lele yang diolah menjadi nugget, ikan lele menjadi pilihan karena memiliki protein hewani cukup tinggi dibandingkan daging sapi sehingga bisa mencegah stunting. Selain mengandung protein hewani yang cukup tinggi, ikan lele juga memiliki harga yang murah dan mudah dibudidayakan oleh masyarakat desa Mentigi. Sosialisasi ini juga memiliki tujuan untuk memberikan pengetahuan yang mendalam mengenai stunting dan memberikan keterampilan baru kepada kader PKK dan warga desa Mentigi dalam mengelola ikan lele menjadi nugget sebagai variasi menu makanan berprotein tinggi serta bergizi pencegah stunting. Metode yang digunakan dalam sosialisasi terobosan baru nugget lele menjadi pilihan asupan gizi ini yaitu pemberian contoh didaktik mengenai penyebab stunting dan akibat dari stunting dan pemberian contoh cara pembuatan nugget lele. Pembuatan ini menghasilkan penambahan pemahaman kader PKK dan warga desa Mentigi terhadap stunting dan olahan nugget lele sebagai variasi menu makanan berprotein dan bergizi dalam rangka penurunan angka stunting di desa Mentigi.